A study of teachers' questioning techniques and its implications for teaching literature in English - Tharmalingam, Selvarajah (August Publishing Sdn Bhd (665084-U), 2014)
Questions are statements that have an interrogative form or function. The effective use of questioning techniques would enable Literature in English teachers to solicit student responses and provide instructional cues that convey the content to be learned or provide directions toward the content to be learned in a literature class. The study investigates teachers’ different questioning techniques and its implication on teaching Literature in English in Malaysian secondary schools. The study examines the types of questions teachers ask in the classroom. The study is carried out in five different schools in Selangor. The data is collected through audio recording of the lessons conducted by the teachers in their respective classrooms, which is then transcribed. The types of questions posed by the teachers are categorized according to the levels of the questions in accordance to Barrett’s taxonomy. Data analysis is carried out to find out the types of questions the teachers employ in Literature in English classroom. The results of the study indicate that the teachers asked many literal level questions. The inadequate usage of ‘high-level’ questions could hinder the development of the students’ critical thinking skills in the classroom. Hence, the study attempts to elaborate on the appropriate questioning techniques that need to be employed by the Literature in English teachers for effective teaching and learning process.